Dual metal NiMo dispersed on silica derived from rice husk ash as a catalyst for hydrocracking of used palm cooking oil into liquid biofuels - Wijaya, Karna; Setyono, Risandrika Dwijayanti Putri; Pratika, Remi Ayu; Heraldy, Eddy; Suseno, Ahmad; Hakim, Lukman; Tahir, Iqmal; Oh, Won-Chun; Saviola, Aldino Javier (Communications in Science and Technology, 2024)
The production of vegetable-based fuels has intensified in recent years due to the decreasing availability of fossil fuels and their environmental impacts. This study explores the synthesis, characterization, and application of nickel-molybdenum (NiMo) bimetal-dispersed silica catalysts for converting used palm cooking oil into liquid biofuels. The catalysts were synthesized using the wet impregnation method, incorporating Ni and Mo metals at concentrations of 1, 2, and 3% by weight of silica derived from rice husk ash. Impregnation of the silica with Ni and Mo metals increased its acidity, with the NiMo/SiO? 2 catalyst exhibiting the highest acidity value of 4.34 mmol/g. This catalyst also demonstrated the largest specific surface area and total pore volume, measured at 205.51 m²/g and 0.88 cm³/g, respectively. Hydrocracking of used palm cooking oil into liquid biofuels was performed at an optimum temperature of 450 °C with catalyst-to-feed weight ratios of 1:100, 2:100, and 3:100 for 1 h by hydrogen gas supply of 20 mL/min. Catalyst activity tests revealed the highest mass percentage of liquid product, 23.3%, at a ratio of 1:100 (w/w), with a biofuel yield of 20.34%, comprising 14.20% gasoline and 6.14% diesel. By utilizing biomass waste as both a catalyst and feedstock, this study presents a sustainable approach to reducing the carbon footprint and promoting environmental balance.